1990
DOI: 10.1111/j.2042-7158.1990.tb07055.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2-mediated Stimulation of Mucus Synthesis and Secretion by Rhein Anthrone, the Active Metabolite of Sennosides A and B, in the Mouse Colon

Abstract: Rhein anthrone, the active metabolite of sennosides A and B, stimulated PGE2 release into the mouse colonic lumen. At 6.24 mg kg-1, it decreased net water and Na+ absorption significantly in the case of water, but could not reverse the net absorption in mouse ligated colon, although it enhanced net K+ secretion. Pretreatment with indomethacin diminished the effects of rhein anthrone except on K+ net secretion. Rhein anthrone or PGE2 markedly stimulated mucus secretion and synthesis in mouse ligated colon. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Caballero-Franco et al (2007) reported a 60% increase in basal luminal mucin content with a probiotic treatment. The mucus layer acts as a barrier between the luminal contents and intestinal nutrient transporters and it protects the mucosal surface from exogenous and endogenous irritants such as bile salts (Yagi et al, 1990). The increase in size and number of intestinal glands and villi could result in increased enzyme pro- duction, resulting in better digestion and absorption of nutrients.…”
Section: Probiotic and Intestinal Morphology Of Turkeysmentioning
confidence: 99%
“…Caballero-Franco et al (2007) reported a 60% increase in basal luminal mucin content with a probiotic treatment. The mucus layer acts as a barrier between the luminal contents and intestinal nutrient transporters and it protects the mucosal surface from exogenous and endogenous irritants such as bile salts (Yagi et al, 1990). The increase in size and number of intestinal glands and villi could result in increased enzyme pro- duction, resulting in better digestion and absorption of nutrients.…”
Section: Probiotic and Intestinal Morphology Of Turkeysmentioning
confidence: 99%
“…Prostaglandins also stimulate mucus secretion in the airways, 48 stomach, 49 colon, 50 and uterus. 51 We show that indomethacin, a cyclooxygenase inhibitor, decreased sPLA 2 -induced mucus secretion, suggesting that cyclooxygenase pathway products may play a role in sPLA 2 -induced mucus secretion.…”
Section: Secretion In Goblet-enriched Cellsmentioning
confidence: 99%
“…The colon was removed and the total colonic fluid was withdrawn and centrifuged at 100,000 g for 20 min at 5°C. According to the modified method of Beubler and Kollar [8], net water flux and electrolyte transport were estimated and expressed as ml water/g tissue and pmol/g tissue, respectively [3], A negative value denotes net absorp tion and a positive value net secretion. Calcium channel blockers were given 30 min before rhein anthrone, except for nicardipine which was given 60 min before.…”
Section: Net Water Flux and Electrolyte Transportmentioning
confidence: 99%
“…The mucus was precipitated using 10% trichloroacetic acid from the colonic tluid and the precipitate was washed with 95% ethanol. The TPBH content was determined photo metrically using galactose as a standard at 540 nm and expressed as mg TPBH/g tissue, according to the meth od of Yagi et al [3].…”
Section: Mucus Secretionmentioning
confidence: 99%
See 1 more Smart Citation